Metabolomic profiling uncovers diagnostic biomarkers and dysregulated pathways in Parkinson’s disease - Chen, Hongfang; Cheng, Xing; Pan, Xiaoling; Yao, Yu; Chen, Lin; Fu, Yaming; Pan, Xinran (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease (PD) is the second most common neurodegenerative disorder, and it has an unclear pathogenesis and lacks validated, specific biomarker-based diagnostic approaches, particularly in PD patients with rapid eye movement (REM) sleep behavior disorder (PD-RBD).MethodsUsing untargeted liquid chromatography-mass spectrometry (LC–MS) metabolomics, serum profiles of 41 drug-naïve PD patients [including 19 PD-RBD and 22 PD without RBD (PD-nRBD) patients] and 20 healthy controls (HCs) were analyzed.ResultsComparative analyses revealed 144 dysregulated metabolites in PD patients versus HCs, with 7 metabolites—sodium deoxycholate, S-adenosylmethionine, L-tyrosine, 3-methyl-L-tyrosine, 4,5-dihydroorotic acid, (6Z)-octadecenoic acid, and allantoin—demonstrating high classification accuracy [area under the curve (AUC) > 0.93]. Compared with PD-nPBD patients, PD-RBD patients exhibited distinct metabolic profiles, characterized by 21 differentially expressed metabolites, including suberic acid, 3-methyl-L-tyrosine, and methyl (indol-3-yl) acetate (AUC > 0.86). Notably, 3-methyl-L-tyrosine displayed dual dynamics, reflecting dopaminergic depletion in PD and compensatory metabolic adaptations in PD-RBD. Pathway enrichment analysis implicated central carbon metabolism (CCM) disruption in PD and peroxisome proliferator-activated receptor (PPAR) signaling pathway inactivation in PD-RBD.ConclusionThese findings reveal potential serum-based biomarkers for PD and PD-RBD, highlight CCM and PPAR pathways as therapeutic targets, and underscore the role of metabolic dysregulation in PD pathophysiology.